Coated pellets with delayed-release glucose for prevention of hypoglycemic episodes - Sabadková Dana; Franc Aleš; Muselík Jan; Neumann David (Acta Pharmaceutica)
Patients tend to prevent hypoglycemia by excessive saccharide intake leading to poorer glycemic control with potentially fatal consequences. This problem could be resolved by means of pellets with glucose release delayed by 120–360 min as a compensation of the antidiabetic drug peak effect. No glucose is released before; hence there is no risk of hyperglycemia and secondary complications. The pellets contain glucose in combination with an osmotically active ingredient and are coated with an ethylcellulose dispersion, which forms an insoluble semipermeable membrane and ensures delayed release. The release of glucose was assessed using dissolution and high-performance liquid chromatography. Dissolution profiles indicated the possibility of achieving the requested lag time using a combination of adequate compositions and coating concentrations. Lag times of 60, 240 and 360 min were achieved. The sample containing carboxymethyl starch was found to be most suitable for the intent of this work.